Proximity mapping of human separase by the BioID approach - Agircan, Fikret Gürkan; Hata, Shoji; Nussbaum-Krammer, Carmen; Atorino, Enrico; Schiebel, Elmar (Biochemical and biophysical research communications, 2016)
Separase is a caspase-like cysteine protease that is best known for its essential role during the metaphase-to-anaphase transition when it cleaves the cohesin ring complex that keeps the sister chromatids together. Another important function of separase is to regulate the process of centriole separation, known as centriole disengagement, at the end of mitosis. We used proximity-dependent biotin identification (BioID) to expand our knowledge on the identity of separase's proximity interactors. We show that separase BioID labeled two domains at the mother centriole: an area underneath the centriolar appendages and another at the proximal end of the mother centriole. BioID analysis identified more than 200 proximity interactors of separase, one being the Alström Syndrome Protein 1 (ALMS1) at the base of centrioles. Other proximity interactors are the histone chaperons NAP1L1 and NAP1L4, which localize to the spindle poles during mitosis and the spindle assembly checkpoint proteins BUBR1, SKA1 and SKA3 that reside at kinetochores in early mitosis. Finally, we show that depletion of BUBR1 homolog from Caenorhabditis elegans delayed the recruitment of separase to mitotic chromosomes, and eventually anaphase onset.
Gesehen am 11.08.2020